Neo-liberal globalism and social sustainable globalisation - Nieuwenhuys, E. C. (Eva Constant), 1951- (International studies in sociology and social anthropology, 2006)
According to mainstream economic thinking, inspired by the ideas of Smith, Ricardo and others, globalisation of the world economy is profitable. But unlike these classic writers, neoliberal economists pay little attention to the moral and social consequences of economic policies. Despite the fact that present social circumstances differ a great deal from those in the time of Smith and Ricardo they keep maintaining that "an invisible hand" will further social ends. In doing so they ignore growing poverty worldwide and the exclusion of countries from the international legal order and of people from the right to social participation and freedom. This book pays attention to economic aspects of globalisation and also to philosophical, legal, social, cultural, ethical and ecological aspects. Its aim is to contribute to possible solutions for worldwide problems that accompany the globalisation process.